EFFECTS OF EMPLOYMENT STRUCTURE CHANGES ON REGIONAL PRODUCTIVITY DISPARITIES IN ROMANIA - Anca Dachin; Raluca Popa (European Regional Science Association (ERSA), 2011)
The sustained economic growth in 2000-2008 in Romania was accompanied by a declining employment rate from 63.6% to 59% in the same period, which improved the overall labor productivity. The unprecedented reduction of labor force participation in some regions was strongly determined by the decline in agricultural employment, negative net migration, as well as increase of social protection. These combined processes were mainly induced by Romania's integration to the EU allowing higher labor force mobility and by social policy measures. In addition, there are longer lasting structural influences, such as the demographic and educational composition of employment. The paper aims at measuring the cross-regional variation of age structure and education levels in Romania and their contribution to regional differences in productivity compared to the most developed region - Bucharest-Ilfov (NUTS2 level). The differences regarding these structures and their changes in the last decade explain partly the territorial polarization of development, which is expected to increase under the impact of the economic crisis.
Keywords: 330